Revision of the leafhopper genus Soractellus Evans (Cicadellidae: Deltocephalinae) with description of a new species from Pakistan - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Soractellus Evans, 1966 is reviewed and a new short-winged species, Soractellus lalianensis sp. nov. from Pakistan, is described and illustrated. A key to distinguish all species in this genus is given.